2006
DOI: 10.1111/j.1527-3466.2006.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide: A Renewed Interest in This Glycosaminoglycan

Abstract: Glycosaminoglycans (GAGs) are the most abundant group of heteropolysaccharides found in the body. These long unbranched molecules contain a repeating disaccharide unit. GAGs are located primarily in the extracellular matrix or on the surface of cells. These molecules serve as lubricants in the joints while at the same time providing structural rigidity to cells. Sulodexide is a highly purified glycosaminoglycan composed of a fast mobility heparin fraction as well as dermatan sulfate. Sulodexide differs from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 66 publications
1
54
0
7
Order By: Relevance
“…Sulodexide (Vessel Due F®) is a specific, highly purified mixture of glycosaminoglycans (a fast-moving heparin fraction with affinity for antithrombin III and a dermatan sulphate fraction with affinity for heparin cofactor II), with a very high tropism for vessel endothelium (90% of the product is found in the endothelium and its concentration is about 20-30 times higher than in other organs) [7][8][9][10][11]. Among its several well recognized activities on blood and vasculature (anticoagulant and venous/arterial anti-thrombotic, hemorrheologic, antiatherosclerotic, antilipidemic and antiproliferative effect), sulodexide is able to guarantee the vessel wall normal permeability, preventing the heparin sulphate degradation, maintaining or restoring the normal electronegativity of vessel walls and inhibiting extracellular matrix expansion between the vessel wall cells, and exibits an antiinflammatory activity [8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulodexide (Vessel Due F®) is a specific, highly purified mixture of glycosaminoglycans (a fast-moving heparin fraction with affinity for antithrombin III and a dermatan sulphate fraction with affinity for heparin cofactor II), with a very high tropism for vessel endothelium (90% of the product is found in the endothelium and its concentration is about 20-30 times higher than in other organs) [7][8][9][10][11]. Among its several well recognized activities on blood and vasculature (anticoagulant and venous/arterial anti-thrombotic, hemorrheologic, antiatherosclerotic, antilipidemic and antiproliferative effect), sulodexide is able to guarantee the vessel wall normal permeability, preventing the heparin sulphate degradation, maintaining or restoring the normal electronegativity of vessel walls and inhibiting extracellular matrix expansion between the vessel wall cells, and exibits an antiinflammatory activity [8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among its several well recognized activities on blood and vasculature (anticoagulant and venous/arterial anti-thrombotic, hemorrheologic, antiatherosclerotic, antilipidemic and antiproliferative effect), sulodexide is able to guarantee the vessel wall normal permeability, preventing the heparin sulphate degradation, maintaining or restoring the normal electronegativity of vessel walls and inhibiting extracellular matrix expansion between the vessel wall cells, and exibits an antiinflammatory activity [8,9,12,13]. Several experimental and human studies demonstrated the favourable anti-proteinuric effect of sulodexide therapy in diabetic patients with nephropathy [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The IV dose of 1200 LRU was selected as a part of a phase I study. Drug compliance was evaluated by questioning the participants and counting the capsules.…”
Section: Study Protocolmentioning
confidence: 99%
“…[1][2][3] Several trials proved that sulodexide is effective in the treatment of diabetic nephropathy and other glomerulopathies, and in the treatment and/or prevention of ischemic cardiovascular events, deep vein thrombosis, venous leg ulcers, cerebrovascular dementia, and complications of peritoneal dialysis. The drug is also protective against endothelial damage, diminishes neointimal proliferation and restenosis of injured arteries, blunts systemic and local inflammation (for review see references [3][4][5][6], and may be used in heparin-induced thrombocytopenia type II. 7 Interestingly, these beneficial effects of sulodexide may be only partially explained by its anticoagulant actions, which suggest some underrecognized mechanisms of the drug.…”
mentioning
confidence: 99%
“…Manufacturers have marketed the drug in many parts of the world for more than 20 years for a range of vascular pathologies. 14 Preliminary studies show that sulodexide reduces urinary albumin excretion rates in patients with type 1 and type 2 diabetes. [15][16][17][18][19][20][21][22] A number of studies suggest different modes of action to explain this phenomenon.…”
mentioning
confidence: 99%